Influence of charge on cell permeability and tumor imaging of GPR30-targeted (111)In-labeled non-steroidal imaging agents - Nayak, Tapan K. (2010)
Recent clinical studies implicate the role of G protein-coupled estrogen receptor, GPR30 in aggressive forms of breast, ovarian and endometrial cancers. However, the functional role of GPR30 at cellular and molecular level remains less clear and controversial, particularly its subcellular location. The primary objective of this study was to develop radiolabeled neutral and charged GPR30-targeted non-steroidal analogues to understand the influence of ligand charge on cell binding, cellular permeability and in vivo tumor imaging. Therefore, we developed a series of GPR30-targeted (111/113)In(III)-labeled analogues using macrocyclic and acyclic polyamino-polycarboxylate chelate designs that would render either a net negative or neutral charge. In vitro biological evaluations were performed to determine the role of negatively charged analogs on receptor binding and activation using calcium mobilization and phosphoinositide 3-kinase assays. In vivo evaluations were performed on GPR30-expressing human endometrial Hec50 tumor-bearing mice to characterize the biodistribution and potential application of GPR30-targeted imaging agents for translational research. In vitro functional assays revealed an effect of charge, such that only the neutral analogue activated GPR30-mediated rapid signaling pathways. These observations are consistent with expectations for initial rates of membrane permeability and suggest an intracellular rather than the cell surface location of functional receptor. In vivo studies revealed receptor-mediated uptake of the radiotracer in target organs and tumors; however, further structural modifications will be required for the development of future generations of GPR30-targeted imaging agents with enhanced metabolic properties and decreased non-specific localization to the intestines.